The Effect of Interfacial Design on the Electrochemical Detection of DNA and MicroRNA Using Methylene Blue at Low‐Density DNA Films. Issue 1 (2nd December 2013) - Tavallaie, Roya; Darwish, Nadim; Gebala, Magdalena; Hibbert, D. Brynn; Gooding, J. Justin
Abstract Herein, we study the effect of interfacial design, specifically the orientation of a DNA probe strand, the length of the diluent and the type of target (DNA vs. microRNA), on the electrochemical response from methylene blue (MB) at low‐density DNA films. The probe DNA interfaces are formed from mixed self‐assembled monolayers of single‐stranded DNA (ss‐DNA) and a hydroxyl terminated alkanethiol diluents on gold surfaces. Variation in the current from the DNA–MB complex after hybridization with complementary and single adenine–cytosine mismatch DNA target is shown to depend on whether the 3′ or 5′ end is tethered to the electrode and the length of the diluent (6‐mercapto‐1‐hexanol vs. 9‐mercapto‐1‐nonanol). The sensors show better mismatch discrimination of single base pairs when both the duplexes are tethered from the 5′ end to the electrode and with a longer‐chain (9‐mercapto‐1‐nonanol) diluent. Of particular note is our demonstration that the DNA/microRNA duplex exhibits greater single adenine–cytosine mismatch discrimination when compared to the corresponding DNA/DNA duplex. This study contributes to the development of selective DNA and microRNA biosensors.